Effect of amorphous silica by rice husk ash on physical properties and microstructures of recycled aluminium chip AA7075 - Mohd Joharudin, N.F.; Abdul Latif, N.; Mustapa, M.S.; Mansor, M.N.; Siswanto, W.A.; Murugesan, J.; Yusoff, F. (Wiley-VCH Verlag, 2019)
High strength to weight ratio of aluminium reinforced as metal matrix composites is a well known material used in automotive application. The effects of recycled aluminium chips AA7075 with amorphous silica by rice husk ash on the physical properties and microstructure were investigated. Recycled aluminium chip AA7075 was reinforced with agro waste of amorphous silica rice husk ash i. e., 2.5 %, 5 %, 7.5 %, 10 % and 12.5 %. Samples of these metal matrix composites were prepared by cold compaction method due to the lower energies consumption and operating cost compared to conventional recycling by casting. Physical testing of density, apparent porosity, water absorption and hardness tests of the metal matrix composites samples were examined in the current study. The density of metal matrix composites was increased up to 5 % of amorphous silica, and then decreased with increasing mass fraction of amorphous silica. Porosity and water absorption of metal matrix composites were significantly consistent at increasing mass fraction of amorphous silica, while the hardness of metal matrix composites was increased at increasing amorphous silica. Consequently, the microstructures of metal matrix composites were observed via optical microscope to analyze the dispersion of the reinforced composites. The microstructures of metal matrix composites were found non-homogeneous and random distribution of amorphous silica and aluminium chip AA7075 compared to 100 % recycled aluminium chip AA7075. Based on investigation to aluminium reinforced rice husk ash composites, it has good potential to improve the material behavior of metal matrix composites by appropriate composition amorphous silica to composite.